Secreción de prolactina en hombres nativos de las grandes alturas - Solís J, José (2011)
Objectives: To determine the effect of chronic hypoxia on prolactin (PRL) secretion. Design: Comparative study. Setting: Endocrinology service, Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Native young men from Lima and Cerro de Pasco. Interventions: Three groups of normal young men age (X24a) with comparable nutritional status, natives from different altitudes: 150 m.a.s.l. (Lima, N=10), 3 000 m.a.s.l. (Tarma, N= 10), 4 200 m.a.s.l. (Cerro de Pasco, n=11); and three patients with chronic mountain disease (CMD) natives from Cerro de Pasco were studied. All subjects were euthyroid and without goiter. RIA determinations of PRL basal serum levels and PRL response to thyrotrophin releasing hormone (TRH) 200 μg I.V. were carried out on each subject. Main outcome measures: Difference of serum prolactin levels and highest response to thyrotrophin releasing hormone in subjects at sea level and at high altitude. Results: Prolactin basal serum levels and the highest response to TRH were significatively less (P<0.05) in high altitude natives when compared to those at sea level. Underlying cause would be chronic hypoxia including either tubero-infundibular dopaminergic system activity increase or lactotrophs’ receptor or post-receptor alteration in high altitude natives. This may be an adaptation mechanism for fertility preservation in high altitude natives. The few patients with chronic mountain disease studied did not allow concluding results, but persistence of less prolactin secretion was observed with late response to TRH. Further investigations in patients with MMD are required to define these observations. Conclusions: Prolactin basal serum levels and highest response to thyrotropin releasing hormone were significatively less in high altitude natives compared with those at sea level.